Application of Sustainable Retrofit in an Educational Building Using BIM - Moreira, Aniele Lacerda; Nahime, Bacus de Oliveira; Paula, Eduarda Ferreira de; Campos, Bruna de Oliveira; Bezerra Filho, César Pereira (Technical and Scientific Journal Green Cities, 2024)
One of the most significant greenhouse gases is CO2 emissions into the atmosphere. The construction stock is associated with one of the highest levels of CO2 emissions, directly related to buildings, raising concerns about the energy crisis and environmental sustainability. The retrofit proposal offers a solution to reduce the impact caused by the construction sector, incorporating renovation and adaptation of obsolete buildings. This research aims to evaluate an educational building with considerable pathologies, a need for accessibility adaptation, and energy, thermal, and lighting deficiencies. It also seeks to develop a retrofit project layout using BIM modeling software and present the institution with relevant proposals to improve the building. After completing the entire process, the study concludes by highlighting the relevance of the retrofit approach, its importance for the construction stock, and its potential to make buildings sustainable, self-sufficient, and a model for future construction, benefiting both the building and the environment.
Keywords: Sustainability; Energy efficiency; Building Information Modeling